THE CHANGES OF MOVEMENTS AND VALUE OF SILAKUPANG PEMALANG TRADITIONAL DANCE - Sari, Iva Ratna; Hartono, Hartno; Florentinus, Totok Sumaryanto (Universitas Negeri Semarang, 2019)
Silakupang is a traditional dance which forms is adjusted to the needs of national dance festival. Besides, the value of the dance is preserved and appreciated by the society. This research aims to analyze the changes of movement and values from Silakupang performance.The research employs qualitative methods with enthnochoreology approach. The data collection of this research used observation, interview, and documentation. The data were validated using triangulation of sources. The analysis of the data uses verification, reduction, and presentation followed by conclusion and interpretation to concept of changing movement and moral value. The finding of the research shows that the most obvious changes are to the choreography, costumes, and background music. The moral value of Silakupangcan be seen from the interpretation of the dance which shows the culture as an identity with moral value and openness to diversity, aesthetics, bravery, and creativity. The most important finding of the research is the changing of choreography which is more expressive and variative with the emphasis on the aesthetics and tolerance to change. The research has a significance in being a guidance for the society in using the traditional dance as the media of education and creativity. The value of Silakupan can be used as the living guidance of the society.